KAJIAN PENERAPAN AKUNTANSI SUMBER DAYA MANUSIA TERHADAP LAPORAN LABA RUGI DAN NERACA DI PT. BPR SINDANG BINAHARTA KOTA LUBUKLINGGAU - Ery Triharyati; Emma Nursita (Universitas Muhammadiyah Bengkulu, 2020)
This study aims to the study of the application of Human Resource Accounting to the Profit Loss and Balance Sheet at PT. BPR Sindang Binaharta Lubuklinggau City. The study application of Human Resource Accounting could be seen by the recording conducted by PT. BPR Sindang Binaharta Lubuklinggau City releted to the cost human resource ( education and training ). Method used in this research is to use descriptive research type, by comparing profit loss and balance sheet before and after the application of Human Resource Accounting. Based on the research, will show those Human Resource Accounting concept giving a bigger net income to income statement. This is raising because cost education and training already in amortisasi and this cost avowed as asset in company. On the balance sheet based on Convensional Accounting and Human Resource Accounting will also showed the raising.This is raising because cost education and training as avowed asset in company.Â Â Keywords : Human Resource Accounting, Profit Loss and Balance Sheet